Requirements for digital educational resources for economic and managerial training of future masters in information technology - Antoniuk Dmytro; Vakaliuk Tetiana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The modern world is rapidly moving towards the digitalisation of the educational process. This movement has accelerated significantly due to several global challenges, such as the COVID-19 pandemic, military conflicts and natural disasters. That is why this study aims to identify the requirements for digital educational resources for the economic and managerial training of future masters in information technology. The article uses the following research methods: analysis and generalisation of experience to determine the requirements for digital educational resources. As a result, the requirements for digital educational resources for the economic and managerial training of future masters in information technology have been determined. All requirements are divided into six areas: pedagogical, content, specific to the IT industry, technological, organisational and user. The pedagogical requirements include professional orientation, interdisciplinarity of digital educational resources, problem orientation, practical value, and content relevance. The content requirements include compliance with educational standards, structured material, multi-level material, availability of practical examples from the IT industry, variety of content formats, relevance of economic data and business cases, and professionalism. Specific requirements for the IT industry include the ability to model business processes, the ability to model IT project management processes, support or integration with project management systems, integration with version control systems, and support for agile development methodologies. Technological requirements include integration with professional/educational tools, support for teamwork, cross-platform, scalability, data security, and responsive design. Organisational requirements include flexibility of learning, modularity, interactivity, multimedia, progress monitoring, and feedback. The user requirements include an intuitive interface, quick access to the necessary information, personalisation of the learning environment, customisation of the interface, offline access to materials, multilingualism, and inclusiveness.